PERAN MOTIVASI DAN DISPLIN DALAM MENUNJANG PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS - Rahman, Rahmania; Fuad, Muhammad (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
This study aims to analyze the role of motivation and discipline in improving student achievement. Learning motivation is an internal and external drive that moves students to achieve learning goals, while learning discipline includes compliance with rules and awareness to organize time and study activities regularly. This study used a descriptive qualitative method with informants selected from junior high school students. Data was collected through observation and structured interviews. The research found this combination of motivation and learning discipline to be a strong synergy in supporting students' learning achievement. Motivation and discipline play an important role in improving student learning outcomes in social studies subjects. Motivation provides the drive to learn and achieve academic goals, while discipline ensures consistency in learning efforts. The implementation of educational strategies that emphasize the importance of motivation and discipline is expected to help students develop their full potential and achieve high learning achievement.